El comercio internacional un instrumento para alcanzar el desarrollo de Costa Rica - Parada Gómez, Álvaro Martín (2013)
Abstract The international trade has been a usefully mechanism to achieve the economic development in developing countries. The advantages of the liberalization of the international trade have impact on exports, investment, production and employment. However, disadvantages are associated with the country size, market failures, government interventions (regulation), among others. The main purpose of this article is to explain the advantages and disadvantages for enterprises and sectors to compete in the international trade. Also, it is essential to suggest strategies to strength the position of the domestic firms in the international market. Two main questions have been including it. The first one, which barriers are facing the enterprises in the developing countries such as Costa Rica to be successfully positioned in the international markets? The second one, which strategy could Costa Rica follows to compete satisfactory in this market? The main conclusion could be that the liberalization of the international trade is one of many mechanisms to achieve the economic development and it is not the only one source of the development to face the multiples necessities of the local society. It is evident that the local government has to intervene using public policies to improve the infrastructure, technology, health, education, among others, as a process to re-strength the role of the international trade in Costa Rica.